Intention to leave a job among public health workers - Tripković, Katica; Šantrić- Milićević, Milena (Medicinski podmladak, 2022)
A particularly important issue in healthcare settings is public health professionals’ intention to leave their job, which may exacerbate both existing and forecasted public health workforce shortage and jeopardize the health system’s performance. The rate of intention to leave a job varies across countries and among different profiles of health workers. It is well documented that job dissatisfaction facilitates the intention to leave. Organizational factors (such as job- related stress, interpersonal relationships with colleagues and supervisors, opportunities for professional development, nature of work, and organizational culture) are considered to have the most significant impact on public health workers’ intention to leave a job. However, the relevance of individual factors (gender, age, marital status) and other factors (e.g., number of family members, community satisfaction, and family responsibilities) is less clear. It is of great importance that policymakers and managers in health facilities implement effective retention strategies in order to reduce public health workers’ turnover and ensure continued delivery of both health care and public health services, and prepare for response to future crises. Retention strategies should be oriented towards ensuring public health workers’ health and safety, increasing job satisfaction, recognizing their value and achievements, and creating supportive and productive work environments.